The effect of medical castration on lipid levels in black South African men with Prostate cancer - Minkowitz, Shaul (University of the Witwatersrand, Johannesburg, 2024)
Background In South Africa, androgen deprivation therapy (ADT) is commonly given as primary therapy for prostate cancer (PCa) due to many patients presenting with advanced disease. The metabolic adverse effects of ADT on lipid profile and weight gain have been reported mainly in Caucasian populations but few studies have been performed in African populations. Men of African descent generally have favorable lipid profiles compared to other populations and our study looked to analyze the effect of medical castration on lipid levels in black South African men with PCa. Methods The aim of this study is to describe the changes in blood total cholesterol, triglycerides, LDL and HDL at 6 months and at 1 year in men with prostate cancer newly initiated on ADT. Changes to BMI, waist circumference and HbA1c were also measured after 1 year of ADT. Our study was conducted at Chris Hani Baragwanath Academic Hospital which is a teaching hospital affiliated with the University of the Witwatersrand. It is located in Soweto, South of Johannesburg and serves the 1.3 million local residents who are predominantly black and of the lower income bracket. This study enrolled 38 black South African men who were starting to receive ADT for PCa. Subjects were evaluated at baseline and at 6 and 12 months. Lipid profiles and HbA1C levels were measured using blood samples and body composition was measure using BMI and waist circumference. Results In this prospective single center study we found that ADT resulted in a significant rise in triglyceride levels and weight gain in black South African men reaching mean levels of obesity using ethnic specific definitions. High density lipoproteins levels decreased significantly particularly in the first 6 months of treatment and thereafter began to rise. ADT also resulted in an increased HbA1C level which is a marker for insulin resistance. Conclusions Androgen deprivation therapy unfavorably changed the body habitus and lipid profile of men with PCa. It was demonstrated that even black South Africans who generally have favorable lipid profiles compared to their counterparts are at risk of developing metabolic syndrome while being treated with ADT
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: Androgen deprivation therapy; Black African men; Metabolic syndrome; Dyslipidemia; UCTD; SDG-3: Good health and well-being